Endometriosis as a cause of chronic pain and deterioration of women's quality of life - etiology, symptoms and treatment method - Bernadetta Wilk; Piotr Stachura; Edyta Witkowska; Marcin Ciechański; Szymon Cholewiński; Klaudia Wilk; Piotr Rejman; Katarzyna Jurkiewicz; Aleksandra Kasprzyk; Katarzyna Pszczoła (Quality in Sport)
Introduction, purpose Endometriosis is a chronic inflammatory condition that primarily affects pelvic tissues, including the ovaries, and is the most common cause of chronic pelvic pain, significantly impacting the quality of life of women of reproductive age. It is currently estimated that up to 10% of women may be affected by this condition. However, diagnosing endometriosis is challenging and often delayed due to frequent misdiagnoses as well as the relatively common occurrence of asymptomatic cases. Several factors may contribute to the development of endometriosis, including anatomical, genetic, and immunological factors. Additionally, it is believed that diet and lifestyle may influence the course of the disease. It is important to remember that beyond reducing overall quality of life and causing chronic pain, endometriosis may also contribute to the development of depressive and anxiety disorders, making it an interdisciplinary health issue.